Numerical study of flows in axial compressors of aircraft gas-turbine engines - Boyko, Ludmila; Dyomin, Alexandr (Eastern-European Journal of Enterprise Technologies, 2018)
Design and adjustment of compressors at modern gas-turbine engines are based on the wide use of numerical analysis methods of a various level of complexity. Such approaches make it possible to analyze the alignment of joint operation of stages and to perform the required correction of geometrical parameters. The methods for calculating the 1D and 2D flow in compressors are distinguished by high flexibility, which allows the utilization of considerable experience in designing and experimental research. These methods are consequently in demand at all stages of the engine life cycle: when creating, adjusting, at operation. We present methods for the calculation of parameters and structure of current, as well as the summary characteristics of axial stages and multistage compressors. To solve a system of motion equations, we employed a matrix method, which makes it possible to apply small computation grids in a flow-through part of the compressor. The method is designed to numerically simulate the sub-, trans-, and supersonic flows in the flow-through part of axial compressor stages and multistage axial compressors at aircraft engines. The methods are implemented in the form of software complexes. The article reports certain results related to the verification of these complexes. We use data from experimental studies into various multi-stage compressors and high-head fan stages. We show a satisfactory agreement between calculated and experimental data over a wide range of modes of consumption and rotation frequency. The developed software package was used to improve the geometrical parameters for an axial multi-stage compressor, aimed at increasing the air flow rate through the compressor and enhancing the reserve of its gas-dynamic stability. Employing small computational grids made it possible to undertake a series of studies, previously available only for the calculation methods of spatial flow. We considered different variants for the execution of the bushing surface at a high-head fan stage. When analyzing the structure of flow in a stage, we show the change in the axial component of velocity in a blade-to-blade channel of the impeller along its axis. Development and application of the new methods of calculation will improve the quality of design of axial compressors and enhance competitiveness of the Ukrainian aircraft gas turbine engines.